E. J. Moeran’s Symphony No. 2 in E flat - Huss, Fabian (Journal of the Society for Musicology in Ireland, 2011)
E. J. Moeran (1894-1950) worked on his Second Symphony from 1939 until the year of his death. Although it remained unfinished, a short-score draft manuscript, in Moeran’s hand, survives in the Moeran collection of the Lenton Parr Library, University of Melbourne. There has been some confusion over Moeran’s progress on the symphony, as well as over the precise dating of the manuscript and what level of completion it represents. The article addresses these issues, reconsiders Moeran’s progress on the work and examines the extant material within the context of the composer’s later life and output. A complete transcription of the manuscript is appended as a supplement to the article, making this material widely available for the first time. Textual issues including unclear passages and omissions, as well as other noteworthy points, are addressed in annotations to the score.